Particle filtering for multi-target tracking and sensor management - Doucet, A; Vo, B; Andrieu, C; Davy, M; ISIF; ISIF (IEEE, 2002)
In this paper, we present computational methods based on particle filters to address the multi-target tracking and sensor management problems. We present a jump Markov model of multi-target systems and an efficient particle filtering algorithm to perform inference. In addition, we also present a formulation of the sensor management problem and its solution using particle methods. © 2002 Int. Soc. of Information Fusion.